Biodiversity of Arbuscular Mycorrhizal Fungi in South America: A Review - Cofré, María Noelia (2019)
Arbuscular mycorrhizal fungi (AMF) are a cosmopolitan group of root symbionts associated with about 80% of earth plants. Current morphological and molecular classification describes around 300 and 1000 AMF taxa respectively. Despite the communities of AMF of many ecological divisions, biomes and ecosystems remain entirely unstudied, cumulative information has increased considerably over the last years, particularly for South America (SA). In this Chapter we reviewed the published literature of AMF morphological richness for SA in order to evaluate richness patterns across the ecological divisions of the region. The compiled data included 2187 records. The 186 morphological taxa identified in the literature evidenced an increasing interest in the study of these fungi in the region, yet with an uneven distribution among ecodivisions within the Amazonia, Atlantic forest, Caatinga and Chaco, which were the main research focus. Glomeraceae species predominated in all ecodivisions with Acaulosporaceae and Gigasporaceae alternated as the second predominant family. It is difficult to draw broad scale conclusions about richness changes among ecological divisions in SA as there are many that remain unstudied and others poorly sampled (e.g. Guianan lowlands and Patagonia respectively). Therefore, further studies of these ecosystems should be encouraged.